Evaluasi Pelaksanaan Rencana Aksi P4GN (Pencegahan, Pemberantasan, Penyalahgunaan dan Peredaran Gelap Narkotika dan Prekursor Narkotika) bidang Pencegahan di Kota Bengkulu - Bobby Mandala Putra; Cica Astika (PUBLIKA : Jurnal Ilmu Administrasi Publik, 2023)
This research aims to provide an assessment of the implementation of the Action Plan for the Prevention, Eradication, Abuse, and Illicit Trafficking of Narcotics and Narcotics Precursors (P4GN) in the prevention field conducted by the National Narcotics Agency of Bengkulu Province. This study utilizes a qualitative method employing a case study research strategy. Data is collected through interviews, observations, and documentation, while data analysis is carried out interactively using the Miles and Huberman data analysis model. The research findings indicate that there are three well-assessed prevention programs/activities and two programs/activities whose implementation needs improvement. The evaluation of the effectiveness of these programs/activities is based on the achievement of P4GN success indicators. The three programs/activities that received positive evaluations are: a) P4GN socialization, b) urine testing for non-civil servant employees and transportation service operators, and c) drug-free village program. On the other hand, the two programs/activities that require improvement are: a) urine testing for every family planning activity, and b) urine testing for core members of the anti-drug youth cadre